Everything is Improvised: How Political Economies of Improvisation Can Invert Critical Social Theories Towards Change for Care and Justice - Gershon, Walter S. (Critical Studies in Improvisation / Études critiques en improvisation, 2026)
This extended abstract simultaneously serves as the contextual information for the accompanying audio paper, a piece of fully sonic scholarship. This work articulates possible trajectories for a political economy of critical improvising. Rather than conceptualizing systems as top-down sociocultural constructions, this audio paper argues that, if everything is at some level improvisational, it is our improvisations that combine to construct our systems of understanding and their production. From this perspective, how one can improvise is an expression of the kinds of possibilities a given system can engender. Conversely, if everything is improvised, one can improvise otherwise towards change. Such a position neither naively negates questions of oppression nor suggests that individual actions alone are enough to make broader social and cultural change. However, such improvisational inversion does provide a modicum of hope in the reorientation of sociocultural structures in ways that reemphasize our individual and collective everyday actions of improvisation.